2019
DOI: 10.1074/jbc.ra118.005309
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-specific Sirt6 deficiency impairs ketogenesis

Abstract: Sirt6 is an NADH (NAD ؉ )-dependent deacetylase with a critical role in hepatic lipid metabolism. Ketogenesis is controlled by a signaling network of hepatic lipid metabolism. However, how Sirt6 functions in ketogenesis remains unclear. Here, we demonstrated that Sirt6 functions as a mediator of ketogenesis in response to a fasting and ketogenic diet (KD). The KD-fed hepatocyte-specific Sirt6 deficiency (HKO) mice exhibited impaired ketogenesis, which was due to enhanced Fsp27 (fatspecific induction of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Mice were injected with CCl 4 to cause liver fibrosis and treated with RGD-Lip/zileuton (10 mg/kg) for 4 h. Primary hepatocytes were isolated as described ( Chen et al, 2019 ). The remaining cells were divided into three groups, fixed, perforated and stained with anti-α-SMA (HSC), anti-F4/80 (Kupffer cells) and anti-CD31 antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were injected with CCl 4 to cause liver fibrosis and treated with RGD-Lip/zileuton (10 mg/kg) for 4 h. Primary hepatocytes were isolated as described ( Chen et al, 2019 ). The remaining cells were divided into three groups, fixed, perforated and stained with anti-α-SMA (HSC), anti-F4/80 (Kupffer cells) and anti-CD31 antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described ( Chen et al, 2019 ). The antibodies were listed in supplementary Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum insulin level was measured by a Rat/Mouse Insulin ELISA kit (EZRMI‐13K, Merck Millipore, Darmstadt, Germany). Levels of hepatic TG, TC, and NEFAs were determined as described 20,22 . All biochemical parameters were measured following the manufacturers’ protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies revealed that fat‐specific Sirt6 ablation sensitizes mice to diet‐induced obesity by inhibiting lipolysis 19 . In the liver, Sirt6 also inhibits the transcriptional expression of Fsp27β by interacting with Crebh, promoting the production of ketone body 20 . In addition to peripheral tissues, Sirt6 has a critical central role in regulating energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%